THE AUTHOR OF JEREMIAH 34:8-22 (LXX 41:8-22): (Acta Theologica)
This article addresses the question as to whether the author of Jeremiah 34:8-22 was a voice for the manumitted Judean debt slaves, who were forced back into slavery during a temporary lifting of the siege of Jerusalem during 589-588 B.C.E. Jeremiah 34:8-22 sets the re-enslavement of these slaves as a precedent that explained the fall of Jerusalem in 587 B.C.E. The allusion in Jeremiah 34:14 to Deuteronomy 15:1, 12 does, however, signify that Jeremiah 34:8-22 echoes the “brother ethics” present in Deuteronomy 15:1-18. The author of Jeremiah 34:8-22 shared the “humanitarian” concerns of the debt release and the slave release laws in Deuteronomy 15:1-18. The debt slaves should have been treated as brothers and not as mere objects. He thus became a voice for these marginalised Judeans.